A history of monetary unions - Chown, John F. (New York : Routledge, 2003)
The main theme of this book is monetary union, how they are created, and how they fall apart.
Includes bibliographical references and index.
osc 2/9/16
Loans
Keywords: Monetary policy --- International; Monetary unions; Economic and monetary union; Monetary unions - history